2002
DOI: 10.1142/s0218863502001103
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Second-Order Nonlinear Optical Properties of Arrays of Noncentrosymmetric Gold Nanoparticles

Abstract: The optical properties of nanoscopic arrays of metal particles are dominated by plasmon resonances and electromagnetic interaction between the particles. We use electron-beam lithography to prepare arrays of noncentrosymmetric gold particles and study their linear and second-order nonlinear optical properties. By varying the orientation of the particles in a fixed lattice, we observe shifts in the polarized linear extinction spectra. The second-harmonic generation efficiencies of the two types of samples diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…These differences would basically be produced by the enhancement produced by metallic nanostructures of the electromagnetic field. Even considering the differences between the nonlinear behavior found in metallic nanoparticles and that found in AsGa-based nanopartices, the authors found that the results presented here are consistent with those obtained in [30,39], since many characteristics are common in both scenarios. The accurate analysis of the metallic nanoparticles is beyond the scope of this paper and will be addressed in the near future.…”
Section: A Quasi-phase Matching In a Homogeneous Layersupporting
confidence: 82%
See 1 more Smart Citation
“…These differences would basically be produced by the enhancement produced by metallic nanostructures of the electromagnetic field. Even considering the differences between the nonlinear behavior found in metallic nanoparticles and that found in AsGa-based nanopartices, the authors found that the results presented here are consistent with those obtained in [30,39], since many characteristics are common in both scenarios. The accurate analysis of the metallic nanoparticles is beyond the scope of this paper and will be addressed in the near future.…”
Section: A Quasi-phase Matching In a Homogeneous Layersupporting
confidence: 82%
“…This example has been simulated previously with the 2D SF-FDTD scheme [29], and it is a well known SHG scenario, in which the phase matching of the second-harmonic field can be easily analyzed. Second, we show the analysis of a 2D L-shaped particle array that has been investigated experimentally and numerically by means of the Fourier modal method (FMM) [30,[39][40][41] and the boundary element method [42]. Here, however, we study dielectric nanostructures only.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Moreover, the locally enhanced field intensities observed in plasmonic structures promise potential for molecular biosensing, [5][6][7][8][9][10] surface enhanced Raman spectroscopy, [11][12][13] and nonlinear optical device applications. [14][15][16][17][18] In planar metallodielectric geometries, surface plasmons represent plane-wave solutions to Maxwell's equations, with the complex wave vector determining both field symmetry and damping. For bound modes, field amplitudes decay exponentially away from the metal/dielectric interface with field maxima occurring at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…E ୨ (ω) and E ୪ (ω) are the two applied electric fields at frequency ω. Because the Cr metal was deposited by e-beam evaporation on the silica substrate, it can be judged to have the isotropic symmetry, and 21 nonzero bulk nonlinear susceptibility elements Γ ୧୨୩୪ are permitted 31,33) . When the nonlinear polarization is along direction 3, the Γ ୧୨୩୪ become Γ ଷ୨୩୪ .…”
Section: Resultsmentioning
confidence: 99%